(untitled) (Development Service Industry Management, 2024)
The article addresses the issue of retaining personnel of domestic enterprises in the conditions of a full-scale war. These issues have become significantly relevant due to the existence of such challenges as large-scale forced external and internal migration of the population, mobilization of men, and the growth of the demographic crisis, destabilization of the domestic labor market, an increase in the number of unemployed, as well as socially vulnerable categories of the population. It is stated that in such critically difficult circumstances, enterprises should develop / adapt their own programs for motivating and stimulating the work of personnel in order to preserve their staff. Accordingly, the purpose of the study was to identify the features and develop an adapted toolkit for motivating enterprise personnel in conditions of full-scale war. The features of motivation of personnel of domestic enterprises in conditions of full-scale war were identified, in particular by types of motivation: direct material; direct intangible; social; psychological; career; educational and socially responsible in the environment of the great war. Tools for motivating personnel of domestic business entities adapted to wartime conditions have been developed, including – transferring employees to work in the rear regions of the country or abroad; financial assistance in the relocation of the employee and his family; ensuring uninterrupted, energy-independent operation of the enterprise; use of remote forms of employment; adjustment of work schedules in accordance with the intensification / weakening of shelling of territories; volunteering and team-building; providing professional and psychological support to staff; guaranteeing stability in employment and wages; financing retraining programs; providing financial support, credits and loans; maintaining ties with employees abroad; hiring IDPs and war veterans; implementation of socially responsible behavior measures for the restoration of territories, infrastructure, assistance to victims. It is argued that further research is important to direct at the development of a state organizational and economic program for the development and effective use of motivational mechanisms for stimulating employment and labor of the population of Ukraine in war conditions.